Influencing Factors of Employee Awareness from Islamic Banking Regarding The Regulations for Development and Reinforcement the Financial Sector - Amanina, Filzah Thahirah; Fianto, Bayu Arie (Jurnal Ekonomi Syariah Teori dan Terapan, 2024)
ABSTRACT This research was conducted to explore the influencing factors of employee awareness from Islamic banking regarding the newly enacted regulations for development and reinforcement the financial sector (P2SK), specifically the Law Number 4 of 2023. Using purposive sampling method, there are 104 samples of Islamic banking employees who met the criteria and then were analyzed using logistic regression technique. The results indicate that age, length of employment, and job position significantly influence the awareness of Islamic banking employees in Indonesia regarding the P2SK  regulations which are categorized into four levels. The limitation in terms of variables and distribution of sample demographics, this research can still be beneficial in theoretical aspects by considering external factors of employees and in practical aspects by evaluating internal policies of Islamic banking or information dissemination processes by the government. Furthermore, this research serves as one of the initial studies addressing employee awareness of a legislative regulation. Keywords: Employee Awareness, Islamic Banking, P2SK Law, Logistic Regression   ABSTRAK Penelitian ini dilakukan untuk mengetahui faktor-faktor yang mempengaruhi kesadaran karyawan perbankan syariah terhadap peraturan pengembangan dan penguatan sektor keuangan (P2SK) yang baru disahkan, yakni Undang-Undang Nomor 4 Tahun 2023. Dengan menggunakan metode purposive sampling, ada 104 sampel karyawan perbankan syariah yang memenuhi kriteria dan kemudian dianalisis menggunakan teknik regresi logistik. Hasil penelitian menunjukkan bahwa umur, lama bekerja, dan posisi jabatan berpengaruh signifikan terhadap kesadaran karyawan perbankan syariah di Indonesia akan peraturan P2SK yang terbagi menjadi empat kategori kesadaran. Penelitian ini memiliki keterbatasan dari sisi variabel dan penyebaran demografi sampel yang digunakan, penelitian ini bisa tetap bermanfaat dari segi teori dengan menggunakan faktor eksternal karyawan dan segi praktik dengan mengevaluasi kebijakan internal perbankan syariah atau proses penyebarluasan informasi oleh pemerintah terkait.  Selain itu, penelitian ini menjadi salah satu penelitian awal yang membahas kesadaran karyawan akan sebuah peraturan perundang-undangan. Kata Kunci: Kesadaran Karyawan, Perbankan Syariah, UU P2SK, Regresi Logistik